The Impact of Financialization on Income Distribution in the USA and Germany: A Proposal for a New Adjusted Wage Share - Petra Duenhaupt (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2011)
Over the recent decades, the USA has witnessed major changes in corporate governance partly due to an overall increase in financialization. The most pronounced development is the escalation of management salaries caused by the rise of stock options. On theoretical grounds, this trend was fostered by advances in the economic discipline of agency theory. In practice, changes in tax laws contributed to promoting the change. Empirical evidence shows that income concentration has increased at the top.This paper contributes to the ongoing debate about income shares by introducing a new adjusted wage share. Arguing that top incomes are closer to profits than to wages, top incomes are removed from the calculation of the indicator. The presented evidence shows that the wage share and the adjusted wage share start to diverge by the end of the 1980s, exactly at the time when the compensation practices of corporations changed considerably. Although shareholder value orientation has increased in Germany as well, business owners are still at the top of the income hierarchy. Therefore, the adjustment of the German wage income share for top management salaries shows only minor discrepancies, which, however, are in the same direction as in the US.
urn:nbn:de:101:1-201202285217
Keywords: E3; E6; H1; 330; Einkommensverteilung; Shareholder Value; Managervergütung; Leistungsentgelt; Lohnquote; USA; Deutschland